2021
DOI: 10.1126/science.abd9776
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear pores dilate and constrict in cellulo

Abstract: Mechanosensitive nuclear pores The nucleus of eukaryotic cells is enclosed by the nuclear envelope, a double membrane punctuated with nuclear pore complexes (NPCs). These giant channels in the nuclear envelope mediate nucleocytoplasmic exchange. Zimmerli et al . show that the mechanical status of the nuclear membranes controls their nuclear pore diameter. Pulling forces imposed through nuclear membranes lead to stretching of NPCs and dilation of their diameter, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
228
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(243 citation statements)
references
References 106 publications
12
228
0
3
Order By: Relevance
“…Rapid assembly during interphase may be dependent on the ability of flexible connectors to form extensive interactions between Nups in different layers, tying these components together quickly and efficiently into the mature inner ring. S. cerevisiae has a closed mitosis; however, the overall architecture of the spoke is highly conserved ( Figure S8 ) ( Zimmerli et al, 2021 ). Partial mitotic disassembly in Aspergillus (a related fungus) is directly dependent on connector-containing Nups (Nup145N, Nup116, and Nup100 [ De Souza et al, 2004 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid assembly during interphase may be dependent on the ability of flexible connectors to form extensive interactions between Nups in different layers, tying these components together quickly and efficiently into the mature inner ring. S. cerevisiae has a closed mitosis; however, the overall architecture of the spoke is highly conserved ( Figure S8 ) ( Zimmerli et al, 2021 ). Partial mitotic disassembly in Aspergillus (a related fungus) is directly dependent on connector-containing Nups (Nup145N, Nup116, and Nup100 [ De Souza et al, 2004 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the number and composition of the outer rings can vary between species ( Bui et al, 2013 ; Kim et al, 2018 ; Mosalaganti et al, 2018 ), and changes in the functional size of the NPC have been observed ( Feldherr and Akin, 1994 ; Mahamid et al, 2016 ). Moreover, recent 3D maps obtained by cryo-ET of cell cryo-sections from C. reinhardtii , S. cerevisiae , S. pombe , and H. sapiens have revealed a large radial expansion of the inner ring ( Mosalaganti et al, 2018 ; Allegretti et al, 2020 ; Zimmerli et al, 2021 ; Schuller et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In other species, hybrids of both arrangements are observed: in the algae Chlamydomonas reinhardtii the nuclear ring consists of 16 Y-complexes but the cytoplasmic ring only of eight [ 33 ]. In the fission yeast Schizosaccharomyces pombe , the nuclear ring also consists of 16 Y-complexes and eight Y-complexes localize to the cytoplasmic site of the NPC which are, however, not connected to a ring-like arrangement [ 34 , 35 ].…”
Section: Nucleoporin Interactions With the Nuclear Pore Membranementioning
confidence: 99%
“…Recent research has begun to elucidate the mechanisms of astrocyte mechanosensation and the significance of this property for physiological astrocyte function in vivo [36,37]. Additionally, nuclear pore complexes, which fuse the two layers of the nuclear envelope, are mechanosensitive thereby making the nucleus itself sensitive to changes in cellular mechanical forces [38][39][40]. The four main contributing factors to the shape of a cell's nucleus are cytoskeletal forces, the thickness of the nuclear lamina, level of chromatin compaction, and activity of proteins that control chromatin conformation [41].…”
Section: Discussionmentioning
confidence: 99%